ALMAGAL - I. The ALMA evolutionary study of high-mass protocluster formation in the Galaxy: presentation of the survey and early results - Molinari, Sergio; Schilke, P.; Battersby, C.; Ho, P. T. P.; Sánchez-Monge, Á; Traficante, A.; Jones, B.; Beltrán, M. T.; Beuther, Henrik; Fuller, G. A.; Zhang, Q.; Klessen, Ralf S.; et al. (Astronomy and astrophysics, 2025)
Context. A large fraction of stars form in clusters containing high-mass stars, which subsequently influences the local and galaxy-wide environment. Aims. Fundamental questions about the physics responsible for fragmenting molecular parsec-scale clumps into cores of a few thousand astronomical units (au) are still open, that only a statistically significant investigation with ALMA is able to address; for instance: the identification of the dominant agents that determine the core demographics, mass, and spatial distribution as a function of the physical properties of the hosting clumps, their evolutionary stage and the different Galactic environments in which they reside. The extent to which fragmentation is driven by clumps dynamics or mass transport in filaments also remains elusive. Methods. With the ALMAGAL project, we observed the 1.38 mm continuum and lines toward more than 1000 dense clumps in our Galaxy, with M ≥ 500 M⊙, Σ ≥ 0.1 g cm−2 and d ≤ 7.5 kiloparsec (kpc). Two different combinations of ALMA Compact Array (ACA) and 12-m array setups were used to deliver a minimum resolution of ∼1000 au over the entire sample distance range. The sample covers all evolutionary stages from infrared dark clouds (IRDCs) to H II regions from the tip of the Galactic bar to the outskirts of the Galaxy. With a continuum sensitivity of 0.1 mJy, ALMAGAL enables a complete study of the clump-to-core fragmentation process down to M ∼ 0.3 M⊙ across the Galaxy. The spectral setup includes several molecular lines to trace the multiscale physics and dynamics of gas, notably CH3CN, H2CO, SiO, CH3OH, DCN, HC3N, and SO, among others. Results. We present an initial overview of the observations and the early science product and results produced in the ALMAGAL Consortium, with a first characterization of the morphological properties of the continuum emission detected above 5σ in our fields. We used “perimeter-versus-area” and convex hull-versus-area metrics to classify the different morphologies. We find that more extended and morphologically complex (significantly departing from circular or generally convex) shapes are found toward clumps that are relatively more evolved and have higher surface densities. Conclusions. ALMAGAL is poised to serve as a game-changer for a number of specific issues in star formation: clump-to-core fragmentation processes, demographics of cores, core and clump gas chemistry and dynamics, infall and outflow dynamics, and disk detections. Many of these issues will be covered in the first generation of papers that closely follow on the present publication.